Radio Astronomical Tools for the Study of Solar Energetic Particles II.Time-Extended Acceleration at Subrelativistic and Relativistic Energies - Klein, Karl-Ludwig (Frontiers in Astronomy and Space Sciences, 2021)
Solar energetic particle (SEP) events are commonly separated in two categories: numerous 'impulsive' events of relatively short duration, and a few 'gradual' events, where SEP-intensities may stay enhanced over several days at energies up to several tens of MeV. In some gradual events the SEP spectrum extends to relativistic energies ($> 1$ GeV), over shorter durations. The two categories are strongly related to an idea developed in the 1960s based on radio observations: Type III bursts, which were addressed in a companion chapter, outline impulsive acceleration of electrons to subrelativistic energies, while the large and the relativistic SEP events were ascribed to a second acceleration process. At radio wavelengths, typical counterparts were bursts emitted by electrons accelerated at coronal shock waves (type II bursts) and by electron populations in large-scale closed coronal structures (type IV bursts). Both burst types are related to coronal mass ejections (CMEs). Type II bursts from metric to kilometric wavelengths tend to accompany large SEP events, which is widely considered as a confirmation that CME-driven shocks accelerate the SEPs. But type II bursts, especially those related to SEP events, are most often accompanied by type IV bursts, where the electrons are rather accelerated in the wake of the CME. Individual event studies suggest that although the CME shock is the most plausible accelerator of SEPs up to some yet unknown limiting energy, the relativistic SEP events show time structure that rather points to coronal acceleration related to type IV bursts. This chapter addresses the question what type II bursts tell us about coronal shock waves and how type II and type IV radio bursts are related with relativistic proton signatures as seen by particle detectors on the Earth and by their gamma-ray emission in the solar atmosphere, focussing on two relativistic SEP events, on 2005 Jan 20 and 2017 Sep 10. The importance of radio emissions as a complement to the upcoming SEP observations from close to the Sun is underlined.